2022
DOI: 10.2166/wh.2022.256
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological, microbiological, and antimicrobial resistance profiles of raw and drinking water in a tourist city in the tri-border region of South America

Abstract: Despite the large amounts of freshwater available in Brazil, the deterioration of surface water can represent a risk of waterborne disease for national and international tourists. The main goal of this study was to assess the quality of drinking water in the triple border region of Brazil before and after being treated in water treatment plants (WTPs) and in Municipal Early Childhood Education Centers (MECECs), in terms of parasitological, microbiological, and physical–chemical aspects. Different water samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous studies in Latin America have found Cryptosporidium spp. in raw and drinking water [85][86][87][88] as well as outbreaks affecting immunocompetent and immunocompromised individuals [64]. Interaction of humans and animals has been growing and becoming closer in recent years increasing the potential for zoonotic transmission, and spread of pathogens such as Cryptosporidium spp.…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies in Latin America have found Cryptosporidium spp. in raw and drinking water [85][86][87][88] as well as outbreaks affecting immunocompetent and immunocompromised individuals [64]. Interaction of humans and animals has been growing and becoming closer in recent years increasing the potential for zoonotic transmission, and spread of pathogens such as Cryptosporidium spp.…”
Section: Plos Onementioning
confidence: 99%
“…In Brazil, the membrane filtration technique is the most used alternative for the research analysis of Giardia spp. cysts in various water matrices (Rosado-García et al, 2017), being detected in raw and treated water from rivers (Scherer et al, 2022;Bonatti et al, 2023), treated sewage (Miglioli et al, 2017), marine and estuarine waters (Leal et al, 2018), and swimming pools (Pineda et al, 2020). However, this technique also presents limitations when used in highturbidity water samples (Coelho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A raíz de las distintas enfermedades ocasionadas por el consumo del agua (Peñafiel Cevallos, 2019), se fueron desarrollando técnicas de desinfección acordes a la tecnología existente durante la historia del ser humano, siendo el hervido una de las primeras técnicas en desarrollarse y actualmente empleada en distintas zonas del mundo, en mejora continua del primitivo proceso (Solano de la Sala et al, 2018). Debido a las enfermedades microbiológicas que surgían en las poblaciones abastecidas de agua (Cano et al, 2021;Scherer et al, 2022), los análisis del elemento significaron un punto de inflexión muy importante y cobraron una alta consideración, siendo a día de hoy un proceso clave en el proceso de abastecimiento de agua de consumo.…”
Section: Introductionunclassified